2017
DOI: 10.4081/ni.2017.6920
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid, kidney function and acute ischemic stroke outcomes in elderly patients: a single-cohort, perspective study

Abstract: Chronic kidney disease and hyperuricemia have been associated to an increased risk and a worse prognosis in acute ischemic stroke. Several mechanisms, including platelet dysfunction, coagulation disorders, endothelial dysfunction, inflammation, and an increased risk of atrial fibrillation could be implicated. The role of serum uric acid in this setting is still object of debate. We enrolled all the consecutive patients admitted to our department for acute ischemic stroke. Cox regression analysis was used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…21 Kidney dysfunction is associated with AF, AF-related comorbidities (including stroke), response to targeted therapies for AF, as well as cognitive decline and dementia. [22][23][24][25][26][27] Highlighting the vascular, kidney, and brain connection, the presence of vascular nephropathy was independently associated with a 15-fold increase in white matter changes found by cranial imaging in a study of 52 patients with chronic kidney disease. 26 As more biomarkers of vascular health are surveyed that involve multiple pathways of vessel physiology, the strength of the association with cerebral vascular injury increases.…”
Section: Discussionmentioning
confidence: 99%
“…21 Kidney dysfunction is associated with AF, AF-related comorbidities (including stroke), response to targeted therapies for AF, as well as cognitive decline and dementia. [22][23][24][25][26][27] Highlighting the vascular, kidney, and brain connection, the presence of vascular nephropathy was independently associated with a 15-fold increase in white matter changes found by cranial imaging in a study of 52 patients with chronic kidney disease. 26 As more biomarkers of vascular health are surveyed that involve multiple pathways of vessel physiology, the strength of the association with cerebral vascular injury increases.…”
Section: Discussionmentioning
confidence: 99%
“…Lorenzo dkk melaporkan bahwa penyakit ginjal kronik dan hiperurisemia berkaitan dengan peningkatan risiko dan prognosis yang buruk pada stroke iskemik akut. 31 Asam urat juga menginduksi stres oksidatif dan disfungsi endotel, sehingga menyebabkan hipertensi sistemik dan hipertensi glomerulus. [30][31] Penurunan laju filtrasi glomerulus (LFG) berkaitan dengan prevalensi yang tinggi untuk terjadinya stroke.…”
Section: Pembahasanunclassified
“…31 Asam urat juga menginduksi stres oksidatif dan disfungsi endotel, sehingga menyebabkan hipertensi sistemik dan hipertensi glomerulus. [30][31] Penurunan laju filtrasi glomerulus (LFG) berkaitan dengan prevalensi yang tinggi untuk terjadinya stroke. Boss dkk melaporkan bahwa penurunan LFG menyebabkan penyakit pembuluh darah kecil tidak hanya pada ginjal tetapi juga pada otak.…”
Section: Pembahasanunclassified
“…Several studies reported poor outcomes in stroke patients with hyperuricemia [7-9]. They reported a dose-dependent relationship between UA levels and stroke outcome [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…They reported a dose-dependent relationship between UA levels and stroke outcome [7, 8]. One reported that UA >7 mg/dL was associated with in-hospital mortality [9], another demonstrated a U-shaped relation [10], and still others reported no particular relationships between UA levels and stroke outcome [11-14]. However, opposite effects have also been reported: hyperuricemia is considered to be a protective factor for stroke [15-20].…”
Section: Introductionmentioning
confidence: 99%